The Relevance Concept of Dawn and Twilight in the Book of Al-Qanun al-Mas’udi for Determine Isya’ and Subuh Pray Time - Nugroho Eko Atmanto (Balai Penelitian dan Pengembangan Agama Semarang, 2012)
Morning dawn and phenomenon twilight phenomenon are interesting for the sci- entists not only for weather forecast and navigation but also setting time prayer times for muslims. The concept of the morning dawn and evening twilight were introduced by al-Biruni in the book Al-Qanun al-Mas’udi. Al-Biruni described the scene at morning dawn and evening twilight in the book Al-Qanun al-Mas’udi and concluded that the twilight occur when the position of the sun is at an altitude of -18°. The concept of al-Biruni is recognized by modern science, astronomy, and the prophetic tradition for its conformity. Besides, the discovery of al-Biruni on the height of the sun is so far used by several religious organizations in some coun- tries to set the time for isha and fajr prayers. By using content analysis, this study discussed the relevance of the concept of morning dawn and evening twilight in the book Al-Qanun al-Mas’udi for determining maghrib prayer time, the praying time for isha and fajr as well.